To multiply the polynomial \((b + 8)(3b - 6)\), we can use the distributive property (also known as the FOIL method for binomials):
- Multiply the first terms: \(b \cdot 3b = 3b^2\)
- Multiply the outer terms: \(b \cdot (-6) = -6b\)
- Multiply the inner terms: \(8 \cdot 3b = 24b\)
- Multiply the last terms: \(8 \cdot (-6) = -48\)
Now, combine all these results:
\[ 3b^2 - 6b + 24b - 48 \]
Combine like terms:
\[ 3b^2 + ( -6b + 24b) - 48 = 3b^2 + 18b - 48 \]
So, the simplified result of multiplying the polynomials is:
\[ 3b^2 + 18b - 48 \]
The correct answer is B) \(3b^2 + 18b - 48\).